2012
DOI: 10.5603/fhc.2012.0054
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glycosylated proteins in cervical cancer recognized by the Machaerocereus eruca agglutinin

Abstract: Abstract:In cervical cancer, glycosylation has been suggested as being involved in both its carcinogenesis and invasive capacity. In this work, we analyzed mucin type O-glycosylation in biopsies of invasive cervical cancer in FIGO stage II B through histochemistry using lectins specific for O-glycosidically linked glycans. Our results reveal that the lectin Machaerocereus eruca (MeA, specific for Gal in a Fuca1,2 (GalNAca1,3) Galb1,4) showed increased recognition of tumoral cells and tumoral stroma tissue comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…regulating immune response and controlling cell metabolism (42,43). In addition, in the G2 phase, de novo synthesis is enhanced to synthesize lipids, which ensures the membrane material needed for mitosis and promotes cell proliferation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…regulating immune response and controlling cell metabolism (42,43). In addition, in the G2 phase, de novo synthesis is enhanced to synthesize lipids, which ensures the membrane material needed for mitosis and promotes cell proliferation (44).…”
Section: Discussionmentioning
confidence: 99%
“…As a glycoprotein on the cell surface, N-Glycon directly affects cell signal transduction and is the diagnostic target of malignant transformation in the early stage of CC ( 39 41 ). O-glycan can be used as a biological marker of proliferation, senescence and metastasis of CC cells by regulating immune response and controlling cell metabolism ( 42 , 43 ). In addition, in the G2 phase, de novo synthesis is enhanced to synthesize lipids, which ensures the membrane material needed for mitosis and promotes cell proliferation ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…HPV can lead to the occurrence of cervical cancer (CESC). Solórzano et al conducted O-glycan analysis of mucins in CESC infected with HPV, and the results showed that HPV infection can cause abnormal fucosylation of mucins, which can affect the invasion of CESC cells [137]. Ahmad et al found that during HCV/HBV infection, the binding of O-glycans at the Ser204 site of insulin-like growth factor to cellular growth factor is reduced, which can lead to the occurrence of HCC [138].…”
Section: Carcinogenic Pathogensmentioning
confidence: 99%
“…Although some proteins that showed at least one predicted N -glycosylation site, they may have been reported with other types of glycosylation. For example, the proteasome alpha subunit (spot 433) has been reported to be O-glycosylated in mouse (Overath et al, 2012); elongation factor 2 (spot 480) is an O-glycosylated protein in human cervical cancer cells (Solórzano et al, 2012), triosaphosphate isomerase (Spots 626 and 649) (Love and Hanover, 2005); and protein Z showed O-glycosylation in human plasma (Spiro, 2002). O-glycosylation occurs in a great variety of proteins that are involved in key nuclear and cytoplasmic activities.…”
Section: Functional Classificationmentioning
confidence: 99%